SPIN 1/2 PARTICLE WITH ANOMALOUS MAGNETIC MOMENT AND POLARIZABILITY - Kisel, Vasily; Bury, Anton; Sachenok, Polina; Ovsiyuk, Elena (Веснік Брэсцкага ўніверсітэта. Серыя 4. Фізіка. Матэматыка, 2024)
Within the general method by Gel’fand – Yaglom, starting with the extended set of representations of the Lorentz group, we construct a relativistic generalized equation for a spin 1/2 particle with two additional characteristics. We take into account the presence of external electromagnetic fields. After eliminating the accessory variables of the complete wave function, we derive the generalized Dirac-like equation, the last includes two additional interaction terms which are interpreted as related to anomalous magnetic moment, and a second additional characteristics looks as related to polarizability of the particle.